3(3x-1)=4(x+3)+5x

Simple and best practice solution for 3(3x-1)=4(x+3)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-1)=4(x+3)+5x equation:


Simplifying
3(3x + -1) = 4(x + 3) + 5x

Reorder the terms:
3(-1 + 3x) = 4(x + 3) + 5x
(-1 * 3 + 3x * 3) = 4(x + 3) + 5x
(-3 + 9x) = 4(x + 3) + 5x

Reorder the terms:
-3 + 9x = 4(3 + x) + 5x
-3 + 9x = (3 * 4 + x * 4) + 5x
-3 + 9x = (12 + 4x) + 5x

Combine like terms: 4x + 5x = 9x
-3 + 9x = 12 + 9x

Add '-9x' to each side of the equation.
-3 + 9x + -9x = 12 + 9x + -9x

Combine like terms: 9x + -9x = 0
-3 + 0 = 12 + 9x + -9x
-3 = 12 + 9x + -9x

Combine like terms: 9x + -9x = 0
-3 = 12 + 0
-3 = 12

Solving
-3 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x+3=7x-1 | | (x+55)=(3x-5) | | 4(7)-12=-5(7)+51 | | x^6-47x^3-8= | | 0.60x+.05(12-x)=.10(-49) | | 2(12)+2x=2(x-2)+2(16) | | 4n+2+4=-6 | | 2(3x-3)+2(x-3)=(2x-1)+(2x-1)+2x | | x^6-47x^3-8=0 | | 3c-4c+1=5+2+3 | | 4y+3y=63 | | 3c+4c+1=5+2+3 | | (x+55)+(3x-5)=180 | | 0.5d=3 | | 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x | | 7=-v-3+6 | | 4(b-2)=(5-b) | | (x+55)+(3x-5)=90 | | 4r^2-r=0 | | 6,5x-9=10,5 | | 2.5d=3 | | 2=5r-3r | | 4q+8=5y | | 6x-2(x+3)=5x-1(+2) | | -6x+5(5x+12)=-168 | | 5y+12x+6=0 | | p-4=-9+9 | | 26-(3x+2)= | | 5x-17=2x+10 | | 22=11k | | 14-x=48 | | 2c-3+9d+7-6d= |

Equations solver categories